ABC News/Washington Post Poll, March 1987 ([Verlag nicht ermittelbar], 1989)
This data collection is part of a continuing series of monthly surveys that evaluate the Reagan presidency and solicit opinions on a variety of political and social issues. Topics covered include in-depth questions concerning Reagan's age, health, memory, and honesty, the impact of his advisers on decision-making, the Iran-contra affair, Reagan's involvement and the Tower Commission report, Republican and Democratic presidential candidates, and the disease AIDS. Demographic characteristics of respondents also were recorded.